Nishapur Revisited : Stratigraphy and Ceramics of the Qohandez. - Rante, Rocco (Oxbow Books, 2012)
Nishapur in eastern Iran was an important Silk Road city, its position providing links to central Asia and China, Afghanistan and India, the Persian Gulf and the west. Despite previous excavations there are many unresolved questions surrounding the site; when was the city founded? Is Nishapur a Sasanian city? Was it founded by the Sasanian king Shapur I or II? The question of chronology of occupation and the ceramic sequence is also problematic particularly for late antiquity and the medieval period, as well as a complete topography of the site. The Irano-French archaeological mission at Nisha.